Advisory Opinion on the Request by the Pan African Lawyers Union Regarding the Compatibility of Vagrancy Laws with the African Charter of Human and Peoples' Rights and other Human Rights Instruments Applicable in Africa (Afr. Ct. H.P.R.). (February 2022) - Kamau, Ndanga
Abstract : On December 4, 2020, the African Court on Human and Peoples' Rights (the Court) issued an advisory opinion on the compatibility of vagrancy laws with the African Charter on Human and Peoples' Rights (African Charter), the African Charter on the Rights and Welfare of the Child (Children's Rights Charter), and the Protocol to the African Charter on Human and Peoples' Rights on the Rights of Women in Africa (Protocol on Women's Rights). In this landmark advisory opinion, the Court considered an important social issue on the African continent.